Distribusi Ukuran dan Tingkat Kematangan Gonad Ikan Julung-Julung Hemiramphus lutkei (Valenciennes, 1847) yang diperdagangkan di Kabupaten Manokwari Papua Barat - Yohanes Aibesa; Mudjirahayu Mudjirahayu; Tutik Handayani; Emmanuel Manangkulangi; Abdul Hamid A. Toha; Fanny F. C. Simatauw; Fitriyah I.E Saleh (Cenderawasih University, 2022)
This study aims to determine the distribution of length to weight, sex ratio, gonad maturity level of julung fish (Hemiramphus lutkei) traded in Sanggeng and Borobudur Manokwari fish markets, West Papua. Research data collection was carried out for ± 1 month, namely February - March 2021, using a descriptive method. The number of fish samples collected was 542 fish. The results of the analysis of the size distribution of julung-julung fish during sampling for body length ranged from 219 – 355 mm for males and 215 -380 mm for females, with a body weight range of 27-53 grams for males and 30-65 grams. The sex ratio analysis of julung julung fish was obtained for males (321 fish) and females (221 fish) significantly different, which means this ratio deviated from the ideal value of 1:1. Based on the results of the analysis show that the value of X2 -count > X2 -table, then H0 is rejected, which means the sex ratio of male and female fish is not balanced from TKG I-VII for males and TKG II-VII for females and mostly found in TKG III conditions. The size of the male julung fish when the gonads first mature was estimated at a length of about 230-260 mm and the female at a size of 250-280 mm. The average Gonad Somatic Index (GSI) of female julung fish was 0.0876 and the standard error was 0.0061 with a GSI range of 0.0092 – 0.7574. The relation- ship between TKG and GSI shows that the increasing stage of fish gonad maturity will be followed by an increase in the value of the fish gonadal index.